Miokardo reperfuzijos adekvatumo po pirminės perkutaninės transliuminės vainikinių arterijų angioplastikos ir stentavimo palyginimas - Vaicekavičius, Edvardas; Grinius, Virgilijus; Navickas, Ramūnas; Unikas, Ramūnas; Janavičius, Arnoldas (Lietuvos chirurgija, 2007)
Edvardas Vaicekavičius, Virgilijus Grinius, Ramūnas Navickas, Ramūnas Unikas, Arnoldas JanavičiusKaunas University of Medicine, Institute of CardiologyE-mail: invlab@kmu.ltBackground / objectiveReperfusion may limit the amount of potentially salvageable ischemic but viable myocardium due to reperfusion damage and injury. The objective of this study was to compare primary percutaneous transluminal coronary angioplasty (PTCA) with stenting according myocardial reperfusion quality in early hospital period.MethodsOne hundred nineteen patients presenting with acute myocardial infarction < 12 hours were treated by primary PTCA or stenting (n = 26). PTCA patients (n = 93) were divided in to 1st group (n = 75) of survived and 2nd group (n = 18) of died patients. Stented patients consisted 3rd gr. (n = 26). The main indications for stenting after angioplasty were: 1) significant (type D, E, or F) dissection of coronary arteries, 2) significant elastic recoil. Peri-procedural TIMI flow, resolution of ST elevation and evolution of ECG stages were used for assessment of reperfusion quality. QRS score and left ventricle EF were used for assessment of LV function.ResultsThe highest TIMI flow, the most intensive resolution of ST, the evolution of ECG stages and the lowest QRS score were noticed for 3rd gr. of stented patients.The died patients (2nd gr.) had lower TIMI flow (p = 0,097472), higher ST (p = 0,0073) and lower EF (p = 0,0005) in comparing with the 1st gr. of patients.ConclusionsThe procedural in-hospital outcome demonstrate that coronary stenting can be used as the primary modality for patients undergoing coronary interventions for acute myocardial infarction, increasing TIMI flow myocardial, reducing reperfusion damage and infarct size.Keywords: myocardial infarct reperfusion, myocardial infarct size, primary percutaneous transluminal coronary angioplasty and stenting.